Primary-Secondary Wavelengths Spectrophotometric Determination of Trace Amounts of Cyanide in Waste Water - Gao, Hong-Wen (Asian Journal of Chemistry, 2012)
In neutral solution and in the presence of isonicotinide the reaction of cyanide (CN-) with barbiturate has been applied for the improvement of cyanide determination in waste water by the updated method named primary-secondary wavelengths spectrophotomethry (PSWS). The result show that the analytical precision and accuracy were increased and gave the higher determination sensitivity than the ordinary spectrophotometry.